ENHANCING COMMUNITY PARTICIPATION IN VILLAGE FUND MANAGEMENT THROUGH “MA FIT MA TOUP” CULTURE IN NORTH CENTRAL TIMOR - Olin, Trinimus (Indonesian Association for Public Administration (IAPA), 2025)
The allocation of village funds in North Central Timor Regency (TTU), which was supposed to be the driver of poverty reduction, did not have a significant effect. The accumulated village funds allocated from 2017 to 2024 reached Rp. 1,084,053,114,000 but could only reduce the poverty rate from 23.52% in 2017 to 20.89% in 2024. One of the factors that is an obstacle in the management of village funds in TTU Regency is that community participation is not ideal. In this context, community participation is still at the level of tokenism, where community involvement is more symbolic and does not influence policy substantially. The main obstacles to increasing community participation include low public literacy towards village fund management, the dominance of local elites in decision-making and the lack of inclusive forums to discuss village policies. On the other hand, there is the cultural value of “ma fit ma toup” that develops in the community, which should be empowered in the framework of easing each other’s burdens and building awareness, responsibility and active participation in development activities in the village. The methodology of this research includes observation, document analysis and interviews with key figures. The results of this study provide information that can be used to direct the community to not only become beneficiaries, but also play an active role in the entire cycle of village fund management, starting from planning, implementation, supervision to evaluation. Community involvement in this cycle will have positive implications for the effectiveness of village fund management which can ultimately reduce poverty rates.